EVALUASI PELAKSANAAN PROGRAM PEMBANGUNAN RUMAH SUSUN SEDERHANA SEWA (RUSUNAWA) DI KOTA BALIKPAPAN - . Arfiansyah (Jurnal Administrative Reform, 2019)
This study aims to find out, analyze, and explain the accuracy of the target group and affordability of the MBR in Balikpapan City flat and the influence of factors in the implementation of the rusunawa development program, which causes a high coverage of residential apartments in Balikpapan City. This research method uses a quantitative method with a formative evaluation approach and descriptive statistical data analysis which is presented in the form of ordinary tables and frequency distribution tables. Test the validity and reliability using the SPSS 16.0 for Windows application. The results of the study showed that the implementation of a flat building development program in Balikpapan City was not as targeted as the target group, namely the MBR because it was inhabited by capable citizens or not the MBR of 38.09%.Keyword: Evaluation, Development, Rusunawa